Persepsi Guru Pamong Terhadap Kompetensi Pedagogik Mahasiswa PPL di Kabupaten Pelalawan - Yunita Purnalika; Nazirun Nazirun (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The background of this research is the implementation of practice in the field which found that students practice experience in managing the teaching and learning process are less effective. Field experience practice students lack mastery of teaching materials so students do not understand the explanations conveyed by field experience practice students. When teaching in class, students are considered as peers, some students are difficult to work with and there are students who are not polite to students in field experience practice. This study aims to describe, analyze, and interpret the perceptions of tutors on student pedagogical competence. This research is quantitative descriptive. The population in this study were all tutors from PPL FKIP UIR students at Pelalawan District High School. This study used a sample of 9 Indonesian tutors in schools where PPL FKIP UIR students carried out PPL activities in Pelalawan District. Data collection techniques using questionnaires and observations. The data analysis technique that researchers did in this study was using percentages. The results showed that the average tutor teacher's perception of the pedagogic competence of PPL students in the Indonesian Language and Literature Education Study Program FKIP UIR for the 2019/2020 Academic Year was 80.90 in the good category with details namely 1) the tutor's perception of the student's ability to understand participants 80.56 in the good category, 2) the teacher's perception of students' ability to design learning is 82.78 in the good category, 3) the tutor's perception of the student's ability to carry out learning is 84.26 in the good category, 4) the tutor's perception on carrying out learning evaluations of 77.78 in the good category, and 5) The teacher's perception of the ability of students to develop students is 76.39 in the good category.